Membangun Toleransi dan Literasi Digital Anak melalui Pendekatan Psikologi Pendidikan dengan Metode Participatory Action Research - Araina Engelina (JURNAL ILMIAH NUSANTARA, 2025)
The rapid development of digital technology requires children, as the digital generation, to have good digital literacy so that they can use technology wisely and responsibly. This study aims to build children's digital literacy and tolerance in an integrated manner through a participatory educational psychology approach. The method used is Participatory Action Research (PAR) by involving children from the GKPB Galang Ning Hyang Sunday School as active agents and students and lecturers as facilitators. Data collection techniques include participatory observation, interviews, and focus group discussions. The results of the study show a significant increase in digital literacy, awareness of tolerance, and children's ability to manage their emotions in facing the challenges of the digital world. These findings prove the effectiveness of the PAR method and the educational psychology approach in producing sustainable positive changes in children's development in the digital age.